KEBERFUNGSIAN KELUARGA PADA KELUARGA DENGAN PASIEN SKIZOFRENIA RAWAT JALAN DI JAKARTA - Sofiana Millati; Fellianti Muzdalifah (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2013)
Abstract The aim of this study is to analyze the family functioning among family with schizophrenic outpatient in Jakarta. The research was conducted in RSKD Duren Sawit and Komunitas Peduli Skizofrenia Indonesia during June-July 2013. This study used quantitative descriptive method. Incidental sampling was used as sampling technique. A total of 107 family members that lived with schizophrenic outpatient participated in this study. Family functioning assessed by self-report questionnaire Family Assessment Device (FAD) based on McMaster Model of Family Functioning. Statistical descriptive that used in this study were performed with SPSS 17.00 for windows. The result of this study showed that family functioning among family with schizophrenic outpatient was unhealthy based on general functioning dimension that assess the overall family functioning. Also found that almost all profiling dimensions of family functioning were unhealthy; communication, roles, affective involvement, and behavior control; except on problem solving and affective responsiveness dimensions were healthy. Keyword: family functioning, family, schizophrenia, outpatient